2014
DOI: 10.1161/hypertensionaha.114.03137
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Birth Weight and Postnatal Weight Gain With Cardiometabolic Risk Parameters at 5 Years of Age

Abstract: Abstract-The present prospective study assessed the impact of birth weight (BW) and postnatal weight gain on blood pressure and metabolic profile during the first 5 years of life. One hundred thirty-nine newborns (63 women) born at term after uncomplicated pregnancies and in the absence of perinatal illness were included. Subjects were divided according to size at birth in small, appropriate, and large for gestational age. After the initial evaluation on the second day of life, infants were followed up at 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 32 publications
3
36
1
Order By: Relevance
“…Consistent with numerous studies, 28,29 our findings demonstrated that low birth weight and premature birth increased the risk of high BP. Low birth weight and prematurity are indicators of poor fetal development and are known as the most powerful clinical surrogates of low nephron endowment, which is an important cause of elevated BP.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with numerous studies, 28,29 our findings demonstrated that low birth weight and premature birth increased the risk of high BP. Low birth weight and prematurity are indicators of poor fetal development and are known as the most powerful clinical surrogates of low nephron endowment, which is an important cause of elevated BP.…”
Section: Discussionsupporting
confidence: 92%
“…Data in the current report by Lurbe et al 2 suggest that metabolic variation may be a seminal mediating link as well. Regardless of weight gain, by age 5 years the SGA group was insulinresistant with lower high-density lipoprotein-cholesterol and higher uric acid levels, compared with the other birth weight groups.…”
Section: See Related Article P 1326-1332supporting
confidence: 49%
“…in Brazil, Crispim et al 7 reported findings similar to those of Lurbe et al, 2 but their study was not prospective. Other issues of interest in the authors' study cohort include the rather high rates of obesity at age 5 years.…”
Section: Perinatal Programming 1167mentioning
confidence: 77%
See 1 more Smart Citation
“…The time immediately before and after birth may be a sensitive period in which multiple interactions between hemodynamic and metabolic parameters foreshadow the clustering of cardiometabolic risk factors later in life (101,102). A critical window of opportunity to modify programming may exist during pregnancy and throughout the first years of life when strategies aiming to reduce risk can be implemented.…”
Section: Birth Weightmentioning
confidence: 99%